Lentivirus-mediated p21/Waf-1 short hairpin RNA enhances the cytotoxic effects and replicative potential of a bladder cancer-specific oncolytic adenovirus in vitro. Issue 1 (January 2017) - Shi, Jie; Fu, Shengjun; Wang, Li; Tao, Yan; Rodriguez, Ronald; Wang, Zhiping
Abstract : Our previous work confirmed that the bladder cancer-specific oncolytic adenovirus Ad/PSCAE/UPII/E1A could selectively replicate in bladder cancer cells, thus causing specific tumor cell lysis. The replicative potential is a crucial factor in determining the therapeutic efficacy of oncolytic adenoviruses. However, viral replication is attenuated by the low-activity promoter that we used, thus compromising viral cytotoxicity. In this study, we investigated the effect of the cell cycle-dependent kinase inhibitor p21/Waf-1 on an adenovirus. We used lentivirus-mediated short hairpin RNA to knock down p21/Waf-1 in two bladder cancer cell lines EJ and 5637. The p21/Waf-1 knockdown not only induced stronger cytopathic effects but also augmented apoptosis, which was closely associated with the enhancement of Fas and the subsequent significant activation of caspase-3. A replicative assay showed that p21/Waf-1 knockdown increased the viral particle production. Western blot analysis confirmed that p21/Waf-1 knockdown upregulated the expression of androgen receptor (AR) and two adenovirus replication indicators E1A and hexon. A luciferase activity assay indicated higher transcriptional activity of the uroplakin II (UPII) promoter in the p21/Waf-1 knockdown cells, and one possible mechanism could be that the increased expression of AR induced the UPII promoter through the AR-binding sites of the prostate stem cell antigen enhancer. These findings indicating that p21/Waf-1 knockdown could enhance cell killing and viral replication have significant implications for the development of bladder cancer-specific oncolytic adenovirus therapies.